A qualitative study of partnership between woman and midwife within midwife-led care clinic - Rizky Vaira; Yanti Yanti; Asri Hidayat (Journal of Health Technology Assessment in Midwifery, 2020)
One indirect causes of maternal mortality in Indonesia is "Three Delays", delays in: (1) deciding to seek appropriate medical help for an obstetric emergency; (2) reaching an appropriate obstetric facility; and (3) receiving adequate care when a facility is reached, which has relation with the lack of women's ability in empowering herself to actively participate and to make suitable decisions about midwifery care they need. The research aims to explore the partnership between woman and midwife in midwifery care. A descriptive qualitative study was conducted using a convenience sample of six low-risk women after they had given birth and six midwives from six geographically distinct midwife-led care clinic in Bantul Regency. Data were collected through semi‑structured in‑depth interviews. The interview was conducted two  to three times and recorded by audio record. Interviews were transcribed and analyzed by the thematic analysis according to Cresswell approach. Seven major themes were identified: (a) midwives ability to partner with women, (b) equality and reciprocity, (c) negotiation, (d) empowerment, (e) trust and time, (f) sharing power and responsibility, and (g) professional friendship. Most of the women are not capable to empower themselves such as less participating in decision making, less considerate in choosing a birthing position, and worsen by the limitations of midwives availability during the delivery process. Midwives need to reflect more the philosophy meaning inside the midwifery care and strengthen the midwifery professionals curriculum in order to persuade women as a partner who capable to empower themselves and to participate actively.